Nostalgia after the communist regime in Romania - Teșculă, Dan (Journal of Education Culture and Society, 2020)
The present paper focuses on the nostalgia after the communist regime in Romania. This small study is a general overview of the progress I have made during the period between march and august on my PhD thesis regarding the nostalgia after the communist regime in Romania. The research methodology used is somewhat new in the field of conteporary history research. The quasi-experimental study was used in order to see if there are significant differences in the way the well-defined social categories perceive the feeling of nostalgia after communism. The period we spanned in this study is the so-called Ceaușescu epoch for wich we have had the most material to work with. From a historiographycal stand-point, the subject is very new, up until now the studies that have appeared during the past years, take the form of articles published in scientific reviews. More studies will eventually show up in the years to come. During this study we have identified small differences between the groups, that posess almost no relevance to our hypothesis. Theoretically educated people know how to present their memories which later have served as an explanation as to why they are not nostalgic. Surprisingly the working class has almost the same perception as the educated people (the intellectuals).